INSTITUTIONAL AND CONCENTRATED OWNERSHIP AND DIVIDEND POLICY OF LISTED OIL AND GAS COMPANIES IN NIGERIA - Zatiock, Asmau Alex; Ango, Yusha’u Ibrahim; Andow, Helen; Dabo, Zainab (Kashere Journal of Management Sciences, 2024)
The main objective of this study was to examine the effect of institutional and concentrated ownership on the dividend policy of listed oil and gas companies in Nigeria. Ex-post facto research design was employed in sampling eight (8) oil and gas companies out of a total population of twelve (12) companies listed on the Nigerian Exchange Group as at December 31st, 2021. Secondary data were extracted from the annual reports and accounts of the sampled companies covering a period of ten years (2012 to 2021). The panel data was analyzed using multiple regression as a technique. The results of the study revealed that institutional ownership (INSTO) has a negative and insignificant effect on dividend policy. Concentrated ownership had a negative and significant effect on the dividend policy of listed oil and gas companies in Nigeria. This means that an increase in the concentration of ownership in the hands of few individuals would reduce dividend policy of oil and gas firms in Nigeria. Block holders (concentrated ownership CNCO) who are often powerful will always demand more returns in the form of dividends which determines the dividend policy of the companies. The study thus recommends that the management of oil and gas companies monitor the proportion of shares held by block holders or a few individuals to ensure that their power is checked.